DOI: 10.1007/978-3-540-69073-3_31
|View full text |Cite
|
Sign up to set email alerts
|

Models in Conflict – Towards a Semantically Enhanced Version Control System for Models

Abstract: For a widespread success of the model-driven paradigm, appropriate tools such as "Version Control Systems" (VCS) are required to adequately support a model-based development process. First attempts to model-based versioning, however, perform conflict detection mainly on basis of a syntactic representation of models without exploiting their semantics. Consequently, in this paper the approach towards a semantically enhanced VCS is presented which enables for semantic conflict detection allowing not only a more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
1
20
0
2
Order By: Relevance
“…Initially, the model-oriented solutions appeared in the studies, where only one of the main configuration management tasks was solved, for example, configuration item identification [10], [2], [13], [6].…”
Section: Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the model-oriented solutions appeared in the studies, where only one of the main configuration management tasks was solved, for example, configuration item identification [10], [2], [13], [6].…”
Section: Related Researchmentioning
confidence: 99%
“…While researching version of controlled solutions, one may encounter model creation [2], [5]. Study [2] describes an algorithm, which consists of meta-model controlled items.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicts may also occur due to same intentions of users who edited a copy of the same artifact (Altmanninger, 2007). For example, a conflict resulting from contradicting intentions is raised if both users rename the same method of a class in a UML class diagram with different intentions.…”
Section: Introductionmentioning
confidence: 97%
“…A more extensive review on refactoring UML models can be found in [22]. An approach of detecting semantically equivalent modeling concepts for structurally different models is described in [23].…”
Section: Related Workmentioning
confidence: 99%